Pemantauan Suhu Air Pada Sistem Tanaman Hidroponik Menggunakan Sensor DS18B20 Waterproof - Wahyu S J Saputra; Faisal Muttaqin (Universitas Darul Ulum, 2021)
Hydroponics is a method of growing plants without using soil media. Some vegetables such as spinach are more suitable to be planted during the rainy season with a cool atmosphere, and some other vegetable crops have different temperature requirements so that environmental temperature monitoring and planting media are very important in the hydroponic method of planting. Temperature is a condition that can be measured using a temperature measuring device called a thermometer. The DS18B20 sensor is one of the sensors that can be used to measure water temperature. In this study, the LCD Matrix which has been connected to Arduino displays data from temperature sensors installed at several measurement points, namely on the storage tube at the bottom and surface and in areas close to the planting media. The temperature generated by the system is then validated using a mercury and alcohol thermometer. The use of a microcontroller can help store temperature changes from time to time and can be displayed again. This makes temperature monitoring activities more effective and efficient.